The Evaluation of Internal Communication at Yogyakarta City Library and Archives Office: A Communication Audit - Alif Pratama, Gusti Panji Alif; Rochimah, Tri Hastuti Nur (Universitas Muhammdiyah Yogyakarta, 2025)
This research aims to evaluate how well the communication system works at the Yogyakarta City Library and Archives Office, focusing on its effectiveness and areas for improvement. It uses a communication audit to analyze the strengths and weaknesses of current communication practices, especially after two significant issues: the recent leadership change that occurred on October 5, 2023, when Afia Rosdiana was appointed as the new Head of the Library and Archives Office, and the implementation of bureaucratic simplification rules in accordance with the Minister of Administrative Reform and Bureaucratic Reform Regulation of the Republic of Indonesia Number 25 of 2021. Both of these issues are of great importance. The study combines both surveys and interviews to gather data, aiming to enhance organizational communication and improve overall performance and public services. There were several communication problems related to the changes in the Head of Office and the Bureaucratic Simplification, including ineffective transmission of information about work tasks and an increase in workload that exceeded capacity.